Hepatic Resection Versus Transarterial Chemoembolization for Intermediate-Stage Hepatocellular Carcinoma: A Cohort Study - Lu, Linbin; Zheng, Peichan; Wu, Zhixian; Chen, Xiong (Frontiers in Oncology, 2021)
Background: The selection criterion for hepatic resection(HR) in intermediate-stage(IM) hepatocellular carcinoma(HCC) is still controversial. We used real-world data to evaluate the overall survival (OS) treated with HR or TACE. Methods: In all, 942 patients with IM-HCC were categorized in HR and TACE group. OS was analyzed using the Kaplan-Meier method, log-rank test, Cox proportional hazards models, and propensity score-matched (PSM) analyses. The smooth curve was performed through the generalized additive model. The interaction test was performed to evaluate the HR impact on OS concerning risk factors. Also, we used multiple imputation to deal with the missing data. Results: Totally, 23.0% (n=225) of patients received HR. At a median overall survival of 23.7 months, HR was associated with the improved OS on multivariate analysis (hazard ratio, 0.45; 95%CI: 0.35, 0.58; after PSM: 0.56; 95%CI: 0.41, 0.77). Landmark analyses limited to long-term survivors of ≥ 6 months, ≥ 1, and ≥ 2 years demonstrated better OS with HR in all subsets (all P< 0.05). After PSM analysis, however, HR increased 20% risk of survival (HR, 1.20; 95%CI: 0.67, 2.15) in the subgroup of LDH ≤192 U/L (P for interaction = 0.037). Furthermore, the significant interaction was robust between the LDH and the HR with respect to 1-, 3-, and 5-year observed survival rate (all P < 0.05). Conclusion: Hepatic resection was superior to TACE for intermediate-stage HCC in the range of LDH level > 192 U/L. Moreover, TACE might be suitable for patients with LDH level ≤ 192 U/L.